2017
DOI: 10.5194/acp-2017-426
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Influence of temperature on the molecular composition of ions and charged clusters during pure biogenic nucleation

Abstract: <p><strong>Abstract.</strong> It was recently shown by the CERN CLOUD experiment that biogenic highly oxygenated molecules (HOMs) form particles under atmospheric conditions in the absence of sulfuric acid where ions enhance the nucleation rate by one to two orders of magnitude. The biogenic HOMs were produced from ozonolysis of α-pinene at 5 °C. Here we extend this study to compare the molecular composition of positive and negat… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
23
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

5
4

Authors

Journals

citations
Cited by 12 publications
(25 citation statements)
references
References 0 publications
2
23
0
Order By: Relevance
“…This is similar to the observations in ref. 15 , where a significant decrease in O:C of the nucleating charged clusters was observed at colder temperatures.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…This is similar to the observations in ref. 15 , where a significant decrease in O:C of the nucleating charged clusters was observed at colder temperatures.…”
Section: Resultsmentioning
confidence: 96%
“…Therefore, temperature likely plays a decisive role, as the saturation concentration has a steep exponential temperature dependence as described by the Clausius–Clapeyron relation. Additionally, a recent study has shown that temperature crucially influences the chemical composition of the initially formed molecular clusters in -pinene ozonolysis ( 15 ). Therefore, the contribution of biogenic organics to new particle formation might be strongly sensitive to temperature.…”
mentioning
confidence: 99%
“…At low temperatures, all HOM species have reduced volatility and thus a larger fraction can participate in particle nucleation and growth -although this is partially compensated for by the slower production rate of HOMs. Temperature also affects the composition and stability of formed HOM clusters (Frege et al, 2017). As a result, the neutral fraction at a given MT concentration is higher at lower temperatures ( Fig.…”
Section: Fraction Of Neutral Particle Formation In Different Chemicalmentioning
confidence: 99%
“…The impact of decreased HOM on new-particle growth rates was compensated by less oxidized species being able to condense at the lower temperatures. In another study, Frege et al (2018) also concluded that HOM formation decreased at lower temperatures, but their study was based on observations of naturally charged ions using an APi-TOF, complicating the interpretation of HOM formation rates.…”
Section: Introductionmentioning
confidence: 99%